What Makes Consumers Buy Pet Food? A Study on Social Media Marketing, Brand Image, Brand Credibility, and Brand Trust toward Purchase Intention for Kitchen Flavor Dry Dog Food - Ivan Bachtiar Pandapotan Nababan; Alfatih S. Manggabarani (CV. Ulil Albab Corp, 2026)
This research investigates the influence of social media marketing, brand image, brand credibility, and brand trust on consumers’ purchase intention toward Kitchen Flavor dry dog food in Indonesia. A quantitative research design was applied, using online questionnaires distributed to 100 respondents selected through purposive sampling. The measurement model was tested using PLS-SEM through SmartPLS 3.0 to assess reliability, validity, and the explanatory power of the proposed framework. The findings show that brand image significantly affects purchase intention, indicating that consumers’ perception of product quality, nutritional benefits, and overall brand reputation plays a key role in their buying decisions. However, social media marketing, brand credibility, and brand trust were found to have no significant direct effect on purchase intention. The structural model demonstrates that 61.3% of the variance in purchase intention is explained by the four predictors. These results highlight that while social media engagement and brand-related perceptions contribute to shaping consumer attitudes, the most influential factor driving purchase intention for Kitchen Flavor is a strong and positive brand image. The study provides implications for pet food brands to enhance brand positioning through value-driven communication, product transparency, and strategic digital engagement.